INTERNATIONAL SECURITY SYSTEM IN THE LIGHT OF CYBER THREATS: LEGAL ISSUES AND PROSPECTS - Troshchenkov, Sergii; Halona, Inesa (Public Management and Policy, 2024)
The study is devoted to systematizing the problems related to cybersecurity in the context of rapid technological development and globalization of the digital space, as well as to finding effective solutions to these problems. The purpose of the study is to identify the main challenges faced by states, organizations and individuals in the field of cybersecurity, as well as to develop recommendations for improving legal and organizational mechanisms for responding to cyber threats. The results of the study, based on the analysis of critical literature and the application of methods of analysis, synthesis, grouping, comparative analysis and modeling, demonstrate a comprehensive understanding of the key challenges in the field of cybersecurity. It is established that the rapid development of technology requires continuous updating of the legal framework to meet modern technological realities, but legislative bodies often fail to adapt to these changes. In addition, significant differences in technological development between countries create unequal opportunities for the protection of information systems at the national level. The problem of incompatibility and inconsistency of international and national norms governing cyberspace leads to legal conflicts and complicates the formation of an effective protection mechanism. A final challenge is defining responsibility and ethical boundaries in cyberspace, which requires international consensus and clear legal definitions. Addressing these challenges requires an integrated approach that includes adapting legal structures to rapid changes in technology, strengthening international cooperation to bridge the technological development gap, harmonizing international and national cybersecurity standards, and clearly delineating responsibilities and establishing ethical boundaries in cyberspace. Such an approach will help ensure sustainability and security in the digital world, adapting to the unpredictable challenges of our time. The practical significance of this study is that it suggests ways to improve the effectiveness of protecting information systems and infrastructures in the face of global cyber threats, which will contribute to ensuring stability and security at the international level. It points to the importance of coordinated interaction between states, academia and the private sector in developing and implementing comprehensive cybersecurity strategies adapted to modern challenges.